2005
DOI: 10.1136/pgmj.2004.031005
|View full text |Cite
|
Sign up to set email alerts
|

Use of the single subject design for practice based primary care research

Abstract: The use of a single subject research design is proposed for practice based primary care research. An overview of the rationale of the design, an introduction to the methodology, strengths, limitations, a sample of recent literature citations, a working example, and possible clinical applications are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…This iterative design has proven to be effective in practice-based research, used since 1945 in drug testing, internal medicine, cardiology, and nutrition (Francis 2005, Newcombe 2005). Single subject design has proven effectiveness when research questions are driven by clinical work with crucial questions, such as adherence to OAs (Janosky 2005). This design supports refining the ADHERE intervention prior to testing, with limited research funds.…”
Section: Methodology and Designmentioning
confidence: 86%
“…This iterative design has proven to be effective in practice-based research, used since 1945 in drug testing, internal medicine, cardiology, and nutrition (Francis 2005, Newcombe 2005). Single subject design has proven effectiveness when research questions are driven by clinical work with crucial questions, such as adherence to OAs (Janosky 2005). This design supports refining the ADHERE intervention prior to testing, with limited research funds.…”
Section: Methodology and Designmentioning
confidence: 86%
“…Because the number of participants is expected to be low, and because of the very variable nature of brain injury, a randomised controlled trial design is not considered appropriate [1]. Instead, a single-subject research design (SSRD, or "n=1" design) [8] is to be employed. In this design, time series data is collected for each participant as they experience different activities or treatments.…”
Section: Research Goals and Methodsmentioning
confidence: 99%
“…This type of research design is known as the single case experimental design, which is both well-suited for busy primary care clinicians and within the purview of doctor of nursing practice (DNP)-prepared NPs. 51 There are several supportive strategies that NPs can offer adults who present with acute bronchitis, which might lead to increased satisfaction and decreased inappropriate antibiotic prescribing. A recent study of 655 adults regarding their behaviors and expectations related to acute respiratory infections found that although most of these individuals expected a prescription for antibiotics and/or a prescription for their symptoms, they also desired Summary of diagnostic and treatment recommendations for adults with acute cough illness *1,2,10,11,13,18,20-27,30,34-38,41-48,52…”
Section: Wwwtnpjcommentioning
confidence: 99%